A new double Z‐scheme TiO2/ZnO‐g‐C3N4 nanocomposite with enhanced photodegradation efficiency for Rhodamine B under sunlight. Issue 1 (5th August 2022) - Hongxia, Jing; Yanlin, Gao; Longxiang, Li; Xu, Wang; Wangjun, Pei
Abstract: The double Z‐scheme TiO2 /ZnO‐g‐C3 N4 nanophotocatalyst was prepared by sol–gel method and solvothermal method. X‐ray diffractometer, FT‐IR, transmission electron microscopy, energy dispersive X‐ray spectrum, ultraviolet–visible (UV–vis), PL, EIS, and so on were used to characterize the structure, morphology, chemical composition, and optical properties of the prepared photocatalyst. And Rhodamine B (RhB) was used as a simulated organic pollutant to study the photocatalytic performance of the photocatalyst. The experimental results show that the double Z‐scheme TiO2 /ZnO‐g‐C3 N4 nanophotocatalyst exhibits high photocatalytic performance under both ultraviolet light and sunlight, and the RhB in the solution can be completely removed in 120 min. This article also proposes a possible Z‐scheme photocatalytic mechanism to explain the increased photocatalytic activity.